Social media charity campaigns and pro-social behavior. Evidence from the Ice Bucket Challenge - Andrea Fazio; Francesco Scervini; Tommaso Reggiani (Masaryk University, Faculty of Economics and Administration, 2022)
Social media play a relevant role in shaping social attitudes and economic behaviors of individuals. One of the first very well-known examples of social media campaign is the Ice Bucket Challenge (IBC), a charity campaign that went viral on social networks in August 2014 aiming at collecting money for the research on amyotrophic lateral sclerosis (ALS). We rely on UK longitudinal data to investigate the causal impact of the Ice Bucket Challenge on pro-social behaviors. In detail, this study shows that having been exposed to the IBC increases the probability of donating money, and it increases the amount of donating money among those who donate at most 100. We also find that exposure to the IBC has increased the probability of volunteering and the level of interpersonal trust. However, all these results, but the one on the intensive margins of donations, have a short duration, limited to less than one year, supporting the prevalent consensus that social media campaigns may have only short-term effects.
Keywords: D64; O35; 330; Donations; Volunteering; Altruism; Social media campaigns; Ice bucket challenge